Enhancing productivity of Chinese hamster ovary (CHO) cells: synergistic strategies combining low-temperature culture and mTORC1 signaling engineering - Shahabi, Farzaneh; Abdoli, Shahriyar; Bazi, Zahra; Shamsabadi, Fatemeh; Yamchi, Ahad; Shahbazi, Majid (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The growing demand for recombinant proteins in medicine has prompted biopharmaceutical companies to seek ways to maximize the manufacturing process. Despite its known negative impact on cell growth, temperature shift (TS) has emerged as a cost-effective strategy to enhance protein quantity and quality in Chinese Hamster Ovary cells (CHO). As cells adapt their growth and protein synthesis rate to the environment through influencing mTOR complex 1 (mTORC1), here we evaluated the potential of mTORC1 signaling engineering to improve the production of granulocyte-macrophage colony-stimulating factor (GM-CSF) protein in stable CHO cells at low temperature. Results: Hypothermic conditions promote the upregulation of mTORC1 inhibitor genes, especially TSC1 and MAPKAPK5, while downregulating S6K, a key effector of the mTORC1 signaling pathway, in CHO-K1 cells. Transcription and protein levels of mTOR increased upon transfection, "pB513-b CMV-P/4shRNAs/GFP" plasmid, "pB513-bHSP90-P/4sh-RNAs/GFP" and pB513B-1 plasmid as mock group in GM-CSF-producing CHO-K1 cells (approximately 60%), along with a high transcript level of S6K. Cell growth-related characteristics were improved, albeit with distinct effects at different temperatures. Notably, these changes were more efficient at 30°C when utilizing the HSP90 promoter, resulting in a three-fold increase in GM-CSF production after three days. Conclusion: This study highlights the importance of temperature regulation and mTORC1 modulation in CHO cellular processes, particularly in recombinant protein production. Understanding these mechanisms paves the way for developing innovative strategies to enhance cell growth, protein synthesis, and overall bioprocess performance, particularly in manufacturing human therapeutic proteins.